EFL Students' Perceptions towards Utilizing Facebook Community Technology to Enhance Business Vocabulary - Yenjai, Sakdipong; Plodkhong, Warakorn; Mongkolnisapakul, Supawan; Bunyang, Titapa; Kanjanapen, Siriporn; Metthamatagul, Hussadin; Nipattamanon, Janejai (Academic and Research Journal of Liberal Arts (Online), 2021)
Recently, English skills are particularly important because one of the elements in learning and using English for all skills for EFL learners is vocabulary size. This study aimed to examine EFL learners' perception of utilizing Facebook Community technology to enhance business vocabulary. Data were collected qualitatively from 51 Thai students studying in the Faculty of Commerce and Management, Prince of Songkla University, Trang Campus, and Rajamangala University of Technology Srivijaya, Songkhla Campus. This study attempted to address EFL learners' perception of utilizing Facebook community technology to enhance business vocabulary by evaluating the data from questionnaires and semi-structured interviews. The results showed a positive perception of EFL learners. The key findings were that Facebook Community was a tool beneficial in business vocabulary learning of EFL learners in (1) ease of access (2) convenience (3) information retrieval to employ in their daily life (4) improving both pronunciation and listening skills, and the vocabulary pronunciation audio posted in Facebook Community is an appropriate method of vocabulary enhancement in EFL learners. This research could be utilized for all educators who are interested in English as a foreign language. The learners will have a favorable perception, affecting their motivation to study further in advanced English. Other instructors might utilize the Facebook Community tool's releasing frequency approach and adapt to their lesson to be widely effective in their classes.